Lionfish: Is It Safe to Eat? - Steve Otwell (EDIS)
Lionfish is not a traditional or likely seafood selection, but growing interest in response to the invasive and increasing abundance has stirred recreational and commercial interest. This prolific, invasive fish is threatening reefs and coastal fisheries in ocean waters throughout the Caribbean Seas and neighboring regions, and eating lionfish is being encouraged as one of the best options to mitigate its harmful impact. This 4-page fact sheet discusses the risks in handling and consuming lionfish, and offers recommendations for avoiding risk, for both recreational and commercial harvesters. Written by Steve Otwell, and published by Florida Sea Grant, April 2015.